Različna pojmovanja znanja - Marjanovič Umek, Ljubica (Sodobna pedagogika, 2008)
By primarily considering recent views on the child's/adolescent's development and education, in the article the author discusses the definition of the term knowledge and, consequently, the understanding of knowledge in relation to its evaluation and assessment. She places the different ways of understanding knowledge in the space between older behavioural and normative development psychology theories and more recent theories that particularly highlight epistemology and metaprocesses; she also explains knowledge concepts by means of the results of empirical research pointing to certain key variables which best explain school knowledge. Afterwards, the author critically assesses various taxonomies of education targets and/or knowledge and, as ahe finds, the frequently simplified transposition of taxonomic levels into criteria for knowledge assessment. She also connects the understanding and assessment of knowledge with the status' and definition of competencies in curricula, especially with regard to the raletionship between the pragmatics of competencies and fundamental or theoretical knowledge.
Keywords: knowledge; znanje; ocenjevanje znanja; learning; učenje; poučevanje